1H NMR spectra of alcohols in hydrogen bonding solvents: DFT/GIAO calculations of chemical shifts. (10th August 2015) - Lomas, John S.
Abstract : Proton nuclear magnetic resonance (NMR) shifts of aliphatic alcohols in hydrogen bonding solvents have been computed on the basis of density functional theory by applying the gauge‐including atomic orbital method to geometry‐optimized alcohol/solvent complexes. The OH proton shifts and hydrogen bond distances for methanol or ethanol complexed with pyridine depend very much on the functional employed and very little on the basis set, provided it is sufficiently large to give the correct quasi‐linear hydrogen bond geometry. The CH proton shifts are insensitive to both the functional and the basis set. NMR shifts for all protons in several alcohol/pyridine complexes are calculated at the Perdew, Burke and Ernzerhof PBE0/cc‐pVTZ//PBE0/6‐311 + G(d, p) level in the gas phase. The results correlate with the shifts for the pyridine‐complexed alcohols, determined by analysing data from the NMR titration of alcohols against pyridine. More pragmatically, computed shifts for a wider range of alcohols correlate with experimental shifts in neat pyridine. Shifts for alcohols in dimethylsulfoxide, based on the corresponding complexes in the gas phase, correlate well with the experimental values, but the overall root mean square difference is high (0.23 ppm), shifts for the OH, CH OH and other CH protons being systematically overestimated, by averages of 0.42, 0.21 and 0.06 ppm, respectively. If the computed shifts are corrected accordingly, a very good correlation is obtained with a gradient of 1.00 ± 0.01, an intercept of 0.00 ± 0.02 ppm and a root mean square difference of 0.09 ppm. This is a modest improvement on the result of applying the CHARGE programme to a slightly different set of alcohols. Some alcohol complexes with acetone and acetonitrile were investigated both in the gas phase and in a continuum of the relevant solvent. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : 1 H NMR spectral shifts for OH and CH protons of alkanols in pyridine and DMSO are estimated by density functional theory/gauge‐including atomic orbital (DFT/GIAO) calculations on alkanol/solvent complexes. Good corrections between computed and experimental data are found, particularly for DMSO.